Study of predictors of quality of life and its association with anxiety and depression in chronic obstructive pulmonary disease in industrial workers - Akhilesh Jain; Richpal Meena; Rekha Sharma; Neelam Yadav; Anadi Mathur; Garima Jain (Wolters Kluwer Medknow Publications, 2020)
Introduction: Chronic diseases such as chronic obstructive pulmonary disease (COPD) have an adverse impact on the quality of life (QOL) of the patient. Anxiety and depression have an association with QOL in COPD. However, this area has not been studied in the Indian subcontinent, especially in reference to the industrial population, which is vulnerable to such chronic disease. The present study aims to assess the prevalence of anxiety and depression and its association with QOL in COPD patients. This study has also examined the other predictive factors associated with QOL in COPD. Materials and Methods: This cross-sectional study involved 50 cases of COPD and an equal number of age- and sex-matched healthy controls. The severity of COPD was classified as per the global initiative for chronic obstructive lung disease recommendation. Participants were assessed for anxiety, depression, and QOL on generalized anxiety disorder 7, Patient Health Questionnaire nine-item and WHOQOL (World Health Organization Quality of Life Instrument)-BREF, respectively. Results: The study sample was predominantly of men (n = 47) with a mean age of 57 years. The mean score of QOL in all domains was significantly lower in COPD cases than control. The prevalence of anxiety and depression was 38% and 44%, respectively, among COPD cases. Odds ratios predicted more risk of developing anxiety and depression in COPD as the OR for depression and anxiety, with 95% confidence intervals were 3.2 (1.2-8.3 and 4.8 (1.8-12.8), respectively. QOL had a strong association with anxiety, depression, chronicity, and the severity of the disease. Conclusion: Anxiety and depression are highly prevalent in COPD and appear to be strong predictors of poor QOL.